Towards a critical edition of Fibonacci’s Liber Abaci - Germano, Giuseppe (Reti Medievali Rivista, 2013)
A group of research working at the University of Naples Federico II aim to achieve the goal to offer a modern scientific and widely accessible edition of Fibonacci’s treatise. With a linguistic-philological, an historical-mathematical and a computer approach it has pointed out the value and the need for a multidisciplinary research in order to achieve the goal of making this edition adequately available to the scientific community.